Strategi Kualitas Layanan dalam Meningkatkan Penjualan pada Usaha Kedai Om Bew & Biliar - Yaafi'ah Aziizah; Faiq Billah; Syahira Fazreen; Faris Faruqi; Hendryadi Hendryadi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase sales by 45% within three months compared to the previous quarter, through enhanced customer satisfaction and loyalty by optimizing service quality at Kedai Om Bew & Billiard, located at Ruko Marco, Jatiluhur, Jatiasih District, Bekasi City, West Java. The activity adopts an action research approach, focusing on employee training to improve service skills and monitoring customer satisfaction through surveys and direct observation. The evaluation of human resource strategies is carried out in cycles, including planning, implementation, observation, and reflection. The results indicate that service quality improvement significantly contributes to customer satisfaction, increasing from 46.5% to 93%, and repeat purchases reach 92%. Thus, improving service quality has proven effective in building customer loyalty and supporting sales growth at Kedai Om Bew & Billiard.